Purification Process Design of Vinyl Acetate Based on Aspen Plus. Issue 1 (July 2020) - Xie, Ya Nan; Meng, Zhi; Li, Fu
Abstract: Based on Aspen Plus process simulation, the purification stage of the production of vinyl acetate by 450000 tons of calcium carbide acetylene process was optimized.The main equipment involved in the process are degassing tower, deacetaldehyde tower, crude separation tower, vinyl acetate refining tower, acetic acid distillation column and so on. The unit operation involved mainly includes general distillation, azeotropic distillation, distillation with side line extraction, absorption, extraction and so on. Aspen Plus sensitivity analysis function is used to analyze and optimize tower parameters such as reflux ratio, the number of theoretical plates, distillate feed ratio, feed position, side line extraction position. The results will provide reference for improving the problems of low purity and energy waste of products.